Morning strength workouts - Lang, Annette, 1959- 4 0 16; 5 (Champaign, IL : Human Kinetics, 2007)
Describes exercise routines, and focuses on early morning workouts, and discusses environment, equipment, and training programs; and also includes detailed exercises for the upper body, core, and lower body.
AM readiness -- Energy to begin your day -- Your workout environment -- Selecting your equipment -- Muscles into action -- Developing your training program -- Workouts for every schedule -- 20-minute programs -- 30-minute programs -- 45-minute programs -- 60-minute programs -- Morning exercises -- Upper body -- Core -- Lower body.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Exercise.;Weight training.;Physical fitness.;Exercise.;Weight lifting.;Physical fitness; 20; 2